Android-based Learning Media Innovation Using Kodular to Improve Mathematical Literacy Skills - Marlina; Syafika Ulfah (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2026)
Mathematical literacy is essential for interpreting and applying mathematical ideas in everyday contexts; however, Indonesian students continue to encounter difficulties in these processes. This study aimed to develop Android-based learning media using Kodular for systems of three-variable linear equations and to evaluate its validity, practicality, and effectiveness. The contribution of this study lies not in the use of Kodular per se, but in the pedagogical alignment of contextual problems, conceptual and video explanations, interactive practice, and assessment tasks with four mathematical literacy indicators: understanding, representation, analysis, and communication. The study adopted a research and development (R&D) design based on the ADDIE model. The participants were 21 Grade 10 students. Data were collected through interviews, expert-validation instruments, response questionnaires, and mathematical literacy tests. The material and media experts assigned validity scores of 69% and 98%, respectively. Practicality scores were 91% from the students and 100% from the teacher. The mean of the individual N-Gain scores was 0.62 (moderate), and the effect size was 2.36 (strong). These results provide preliminary evidence that the developed media was valid, practical, and effective within the study context. The study contributes a literacy-oriented pedagogical design delivered through Kodular rather than an innovation based solely on the development platform.